2017
DOI: 10.1039/c6cs00931j
|View full text |Cite
|
Sign up to set email alerts
|

Operando chemistry of catalyst surfaces during catalysis

Abstract: Chemistry of a catalyst surface during catalysis is crucial for a fundamental understanding of mechanism of a catalytic reaction performed on the catalyst in the gas or liquid phase. Due to the pressure- or molecular density-dependent entropy contribution of gas or liquid phase of the reactants and the potential formation of a catalyst surface during catalysis different from that observed in an ex situ condition, the characterization of the surface of a catalyst under reaction conditions and during catalysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 200 publications
0
124
0
Order By: Relevance
“…Hence, operando methodology describes in situ spectra under true catalytic operation as determined by simultaneous online activity/selectivity measurements. Determination of intrinsic reaction kinetics of catalyzed reactions is of importance in the safe and economical design and control of industrial chemical and environmental processes, and in the development of new and improved catalysts . Echoing all the assertions in this review, operando studies have shown that catalysts may undergo dynamic structural transformations upon small changes in the reaction conditions and such transformations have a strong impact on the performance of the catalysts .…”
Section: Experimental Detection Of Metastable States In Catalysismentioning
confidence: 91%
“…Hence, operando methodology describes in situ spectra under true catalytic operation as determined by simultaneous online activity/selectivity measurements. Determination of intrinsic reaction kinetics of catalyzed reactions is of importance in the safe and economical design and control of industrial chemical and environmental processes, and in the development of new and improved catalysts . Echoing all the assertions in this review, operando studies have shown that catalysts may undergo dynamic structural transformations upon small changes in the reaction conditions and such transformations have a strong impact on the performance of the catalysts .…”
Section: Experimental Detection Of Metastable States In Catalysismentioning
confidence: 91%
“…Surface science techniques and scanning tunnelling microscopy (STM) are tools of choice for studying basic catalytic processes thanks to their ability to provide unique characterization of the structural and electronic state of the catalyst surface at the nanoscale . Notably, real‐space imaging with molecular resolution allows discriminating between the different reaction products occurring possibly simultaneously on the surface ,…”
Section: Figurementioning
confidence: 99%
“…[25] The laboratorybased NAP-XPS system is even availablef or daily catalyst studies. [25] The laboratorybased NAP-XPS system is even availablef or daily catalyst studies.…”
Section: Advances In Catalyst Characterizationmentioning
confidence: 99%
“…[25] Under thesec onditions, photoemission from the gas phase may overcome surface-bound contributions. [25] Under thesec onditions, photoemission from the gas phase may overcome surface-bound contributions.…”
Section: Bridging the Pressuregapmentioning
confidence: 99%